A Systematic Review on Outcomes of Anterior Skull Base Reconstruction. Issue 11 (November 2020) - Lim, Xuxin; Rajagopal, Rajini; Silva, Priyamal; Jeyaretna, Deva Sanjeeva; Mykula, Roman; Potter, Matthew
Summary: Introduction: Anterior skull base resection often results in large defects that need to be reconstructed. This can be done using loco-regional, free flaps or both. Objective: The aim of this systematic review is to evaluate the surgical outcomes (mortality, complication rates and functional outcomes) for patients undergoing anterior skull base reconstruction. Methods: Electronic databases (MEDLINE, EMBASE and Scopus) were systematically searched for relevant articles from 1974 to March 2018. A total of 41 studies were included in this systematic review. No randomized controlled trials were identified; therefore, a meta-analysis was not performed. Results: Mortality from anterior skull base reconstruction were about 0–4% for loco-regional flaps while free flaps were around 0–7%. Overall complications ranged from 0% to 43% in loco-regional flaps, while rate of complications for free flaps ranged from 25% to 66.7%. Flap complications ranged from 0% to 14% for free flaps and 0% to 35% for local flaps. Quality-of-life measures did not differ significantly depending on surgical approach but were worse for patients with malignancies. Conclusion: Due to varying standards of reporting of outcomes, lack of a standardized classification system for anterior skull base defects and absence of clinical trials, we were unable to perform a meta-analysis in this systematic review. Recommendations to guide future studies are proposed.